2017
DOI: 10.1055/s-0043-100215
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete resection rate of cold snare polypectomy: a prospective single-arm observational study

Abstract: Cold snare polypectomy (CSP) is considered to be safe for the removal of subcentimeter colorectal polyps. This study aimed to determine the rate of incomplete CSP resection for subcentimeter neoplastic polyps at our center. Patients with small or diminutive adenomas (diameter 1 - 9 mm) were recruited to undergo CSP until no polyp was visible. After CSP, a 1 - 3 mm margin around the resection site was removed using endoscopic mucosal resection. The polyps and resection site marginal specimens were microscopical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 25 publications
4
76
2
1
Order By: Relevance
“…In addition, some studies have shown that CP is useful for removing polyps of more than 10 mm in size [22-24]; however, some of those reports recommend piecemeal polypectomy. The reported rate of incomplete resection by CP was 3.9% [25] and there is a report of recurrence after CP [26]; thus, careful consideration for the indication of size is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have shown that CP is useful for removing polyps of more than 10 mm in size [22-24]; however, some of those reports recommend piecemeal polypectomy. The reported rate of incomplete resection by CP was 3.9% [25] and there is a report of recurrence after CP [26]; thus, careful consideration for the indication of size is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Cold snare polypectomy (CSP) was originally used to remove small colorectal polyps (≤10 mm), and its efficacy and safety were reported [25]. Recently, CSP is used for small SNADETs.…”
Section: Characteristics and Treatment Outcome Of Each Er Methodsmentioning
confidence: 99%
“…4 Cold snare polypectomy (CSP) for subcentimeter polyps drastically prevails 5 and is expectedly associated with less delayed bleeding, coagulation syndrome, and perforation. 8 However, Tutticci et al 9 reported that cold snare defect protrusions (CSDPs) occurred in 14% of patients after CSP, and pathological muscularis mucosa was present in 80% of CSDPs. 8 However, Tutticci et al 9 reported that cold snare defect protrusions (CSDPs) occurred in 14% of patients after CSP, and pathological muscularis mucosa was present in 80% of CSDPs.…”
Section: Introductionmentioning
confidence: 99%